2012
DOI: 10.7763/ijtef.2012.v3.190
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Herd Behavior: An Empirical Evidence from Indian Equity Market

Abstract: The paper aims to study the effect of herding in Indian equity market. The authors have tested the presence of herding using data from National Stock Exchange (NSE) and methodology as described in Christie and Huang (1995) and Chang, Cheng and Khorana (2000). Security return dispersion as a function of aggregate market return has been taken as a proxy for herd behavior. To test the presence of herding linear regression model and linear regression using quadratic functional form has been applied. Previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
23
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 10 publications
9
23
2
2
Order By: Relevance
“…They further suggested that market stress can rather help bring the market to equilibrium. Consistent with the findings of Lakshman et al (2008), Prosad, Kapoor and Sengupta (2012) found no evidence of herding in the Indian Stock Market over the period 2006 to 2011 using a sample of Nifty50 stocks (a stock index for 22 sectors of the economy of India). Contrary to the findings above, Farber, Nguyen & Vuong (2006) confirmed the existence of herding on the Ho Chi Minh City Securities Trading Center (HSTC) in Vietnam in stressful market conditions.…”
Section: Literature Reviewsupporting
confidence: 86%
“…They further suggested that market stress can rather help bring the market to equilibrium. Consistent with the findings of Lakshman et al (2008), Prosad, Kapoor and Sengupta (2012) found no evidence of herding in the Indian Stock Market over the period 2006 to 2011 using a sample of Nifty50 stocks (a stock index for 22 sectors of the economy of India). Contrary to the findings above, Farber, Nguyen & Vuong (2006) confirmed the existence of herding on the Ho Chi Minh City Securities Trading Center (HSTC) in Vietnam in stressful market conditions.…”
Section: Literature Reviewsupporting
confidence: 86%
“…In contrast to [27], they suggested that herding can be more pronounce before market stress, rather than during market stress since market crisis can lead to market equilibrium. Contrary to the results of [23] who discovered herding in emergent economies such as South Korea and Taiwan; [30] used daily data of fifty (50) from the period of April 2006 to March 2011 and did not find herding in the Indian stock market. Nevertheless, individual tests for bull and bear periods of the market show that herding is detected in larger degree in bull period.…”
Section: Empirical Reviewcontrasting
confidence: 58%
“…Iyer and Bhaskar (2002) have explored the role of psychology in investors' stock trading behaviors in India. Prosad et al (2012) find evidences in favor of the standard finance implications and rejects herding behaviors in Indian markets. Sahni (2012) has explored the loss aver-ness behaviors and the effects of anchoring on the Indian stock traders.…”
Section: Research Gapsmentioning
confidence: 87%